Limiting eigenfunctions of Sturm–Liouville operators subject to a spectral flow - Beck, Thomas; Bors, Isabel; Conte, Grace; Cox, Graham; Marzuola, Jeremy L. (Annales mathématiques du Québec, 2021)
We examine the spectrum of a family of Sturm–Liouville operators with regularly spaced delta function potentials parametrized by increasing strength. The limiting behavior of the eigenvalues under this spectral flow was described by Berkolaiko et al. (Lett Math Phys 109(7):1611–1623, 2019), where it was used to study the nodal deficiency of Laplacian eigenfunctions. Here we consider the eigenfunctions of these operators. In particular, we give explicit formulas for the limiting eigenfunctions, and also characterize the eigenfunctions and eigenvalues for all values for the spectral flow parameter (not just in the limit). We also develop spectrally accurate numerical tools for comparison and visualization.